Cinara pinihabitans (Mordvilko, 1895) in der Steiermark (Österreich) wieder aufgefunden (Homoptera: Lachnidae). - Fossel, Annemarie (Contributions to Entomology = Beiträge zur Entomologie, 1969)
Comparisons of the author's finds with the descriptions of the types of Mordvilko by Szelegiewicz establish beyond doubt that the genuine Cinara (C.) pinihabitans (Mordvilko, 1895), missing for a long time, has suddenly reappeared and lives not only in the vicinity of Warsaw but also in the Alps. In the Alps it appears to be very stationary though it does not occur every year. In the years 1960 to 1963 and again in 1966 it appeared in exactly the same places and inhabited both pine and dwarf pine. As in the summer the waxed C. pinihabitans can hardly be distinguished from the slender C. pini, with whitch it even forms mixed populations, it is probable that it was often overlooked. Therefore it should be collected preferably in late autumn when the area of its distribution can be better determined. The widely scattered finds suggest that the species has a wider distribution than it was assumed and that it may be found perhaps not only in Estern Europe and in the Alps. Unfortunately i can not yet say anything about its habits, its cycle of generations, its fundatrix and its first appearance.